Compendium of Key Documents relating to Peace and Security in Africa - Monica Juma (Pretoria University Law Press (PULP), 2006)
Compendium of Key Documents relating to Peace and Security in Africa Edited by Monica Juma 2006 ISBN: 0-9585097-3-5 Pages: 521 Print version: Available Electronic version: Free PDF available
English